Gravity‐wave‐induced perturbations in marine stratocumulus. (17th May 2012) - Allen, G.; Vaughan, G.; Toniazzo, T.; Coe, H.; Connolly, P.; Yuter, S. E.; Burleyson, C. D.; Minnis, P.; Ayers, J. K.
Abstract We discuss the role of atmospheric gravity waves in modulating cloud radiative and dynamical properties over the southeast Pacific. Satellite imagery and satellite‐retrieved cloud properties during October 2008 illustrate three distinct episodes of horizontal propagation of gravity wave trains across the large‐scale stratocumulus (Sc) cloud deck capping the local marine boundary layer. In one period, 7–9 October 2008, the waves modulated cloud‐top‐height by up to 400 m peak‐to‐trough, propagating perpendicular to the synoptic boundary layer flow with phase speed 15.3 m s−1, period ∼1 h and horizontal wavelength 55 km. The gravity waves were observed to be non‐dispersive. These waves were first evident in the cloud deck near 30°S, 85°W during a 24 h period beginning at midday on 7 October 2008, and propagated northeastward toward the Peruvian coast for the following 48 h. During this time they induced both reversible and non‐reversible changes in cloud‐radiative and cloud‐dynamic properties, such that areas of clear sky developed in the troughs of passing wave‐fronts. These pockets of open cells persisted long after the passage of the gravity waves, advecting northwestward with the background wind. Using the analysis fields of the European Centre for Medium‐Range Weather Forecasts in conjunction with infrared and microwave satellite imagery, we show that these gravity waves emerged from a disturbed subtropical jet stream. The radiant of the waves was coincident in all cases with centres of large negative residuals in nonlinear balance, suggesting that geostrophic readjustment of sharply divergent flows associated with the disturbed jet provided a source for the wave energy. Conversely, gravity waves were not observed in more quiescent jet conditions. This case study highlights the important and irreversible effects that gravity waves propagating in the troposphere can have on cloud radiative properties (and hence surface radiation budgets) over a very wide area. It also highlights the importance of synoptic influence on Sc‐covered marine boundary layers. Copyright © 2012 Royal Meteorological Society